An analysis of non-financial indicators as a tool for assessing the performance of a company: a case of BancABC - Takaendesa, Albert T. (Midlands State University, 2018)
Investors as the major stakeholders of organisations have in the past become the sole focus of annual reports. The research investigated the use of alternative performance measurement systems for the purpose of reporting on information that caters for all stakeholders. BancABC has been focusing on financial indicators as a performance assessment tool for reporting purposes. This focus on financial performance has caused problems such as lack of information with a future orientation, an incomplete picture of the organisation and an internally focused reporting structure. Challenges faced in using non-financial indicators were investigated and discovered namely lack of the knowledge, choosing inappropriate indicators and failure to link the measures with organisational goals. The research recommended that management revise the reporting structure to incorporate non-financial performance indicators for all stakeholders.